The Environmental Graphic Design in Commercial Interior The Case of Pakuwon-Supermal Surabaya - Yauwerissa, Elizabeth Christy; Kusumowidagdo, Astrid (Serat Rupa: Journal of Design, 2025)
The objectives of this research are to understand how Environmental Graphic Design (EGD) contributes to shaping consumer perceptions and enhancing the shopping experience. The research method is qualitative research, which provides an in-depth understanding of social phenomena by emphasizing non-numerical data collection and analysis. In this study, visual observation is employed as the primary data collection technique, allowing for a detailed exploration of human interactions and environmental dynamics within the context of Pakuwon-Supermal Surabaya. The data collection process involves direct observation, where object, behaviors, interactions, and environmental factors are systematically documented through photographs. Designing engaging brand experiences, effective space circulation enhances visitor movement throughout the mall, encouraging exploration and engagement. Additionally, the design of spaces significantly impacts brand identity and presence, as unique architectural forms create memorable experiences aligned with brand values. Decorative structures strategically placed within the environment elevate brand presence, reinforcing recognition and emotional connections. Furthermore, well-designed public facilities enhance accessibility and comfort, contributing to an overall positive visitor experience. This research offers valuable insights for architectural interior designers and other stakeholders involved in commercial branding. By strategically implementing EGD, shopping centers can improve brand perception and consumer satisfaction within their environments.